2013
DOI: 10.1101/gr.157339.113
|View full text |Cite
|
Sign up to set email alerts
|

Derived variants at six genes explain nearly half of size reduction in dog breeds

Abstract: Selective breeding of dogs by humans has generated extraordinary diversity in body size. A number of multibreed analyses have been undertaken to identify the genetic basis of this diversity. We analyzed four loci discovered in a previous genome-wide association study that used 60,968 SNPs to identify size-associated genomic intervals, which were too large to assign causative roles to genes. First, we performed fine-mapping to define critical intervals that included the candidate genes GHR, HMGA2, SMAD2, and ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(196 citation statements)
references
References 59 publications
11
184
1
Order By: Relevance
“…These regions varied largely in size (750,000-6,250,000 bp, median 1,500,000 bp), and contained 646 genes in total. Within the most differentiated regions we noticed several genes previously associated with size or skeletal features in other species including LCORL-NCAPG (e.g., Gudbjartsson et al 2008;Rubin et al 2012;Tetens et al 2013;Sahana et al 2015), STC2 (Gagliardi et al 2005;Rimbault et al 2013), HOXD cluster (Zakany and Duboule 2007), COL11A1 (Li et al 1995;Annunen et al 1999), and IGF2BP2 (Dai et al 2015) (Figure 4A). …”
Section: Genome-wide Scan For Signatures Of Selection In Netherland Dmentioning
confidence: 72%
“…These regions varied largely in size (750,000-6,250,000 bp, median 1,500,000 bp), and contained 646 genes in total. Within the most differentiated regions we noticed several genes previously associated with size or skeletal features in other species including LCORL-NCAPG (e.g., Gudbjartsson et al 2008;Rubin et al 2012;Tetens et al 2013;Sahana et al 2015), STC2 (Gagliardi et al 2005;Rimbault et al 2013), HOXD cluster (Zakany and Duboule 2007), COL11A1 (Li et al 1995;Annunen et al 1999), and IGF2BP2 (Dai et al 2015) (Figure 4A). …”
Section: Genome-wide Scan For Signatures Of Selection In Netherland Dmentioning
confidence: 72%
“…Similar findings have recently resulted from genetic studies of domestic dogs, which show the greatest variation in body size of any land mammal (45). It was found that the occurrence of derived variants at only six genes is a major explanation for the extreme reduction in body size of dogs caused by selective breeding (46). The authors found STC2 to be among the genes, also including IGF1 and IGF1R.…”
Section: Discussionmentioning
confidence: 99%
“…We initially identified two loci on the X chromosome spanning several megabases (Mb) as contributors to body size in large breeds through a GWAS of 915 dogs representing 80 domestic dog breeds [22]. The result has since been replicated by several groups [22,23,47,48]. No study, however has explored the result in detail, in part because the lack of heterozygosity on the canine X chromosome can reflect popular sire effects, which may complicate fine mapping efforts.…”
Section: Introductionmentioning
confidence: 99%